METAMORPHIC CONDITIONS OF ULTRAMAFIC LENSES FROM THE EASTERN SØR RONDANE MOUNTAINS, EAST ANTARCTICA - MAKIMOTO, Hiroshi; ASAMI, Masao; GREW, Edward S. (National Institute of Polar Research, 1990)
P(論文) Lenses up to 5m in size of ultramafic rocks occur in quartzo-feld-spathic, locally migmatized, gneisses at four localities of the eastern Sør Rondane Mountains. A composite lens at one locality consists of harzburgite, orthopyroxenite and garnet amphibolite, and a second, consists entirely of harzburgite. Harzburgite contains chromite-poor spinel (Cr/(Cr+Al)～0.1), which indicates that it was equilibrated under conditions of the spinel lherzolite facies. Temperature estimates for the ultramafic lenses represent that they preserved at least two stages of metamorphic temperature conditions. The higher temperatures (～750℃) estimated by the maximum Al-content of orthopyroxene and the pyroxene geothermometers are consistent with those of the early granulite-facies metamorphic event reported in the eastern Sør Rondane Mountains. This indicates that the ultramafic lenses and the surrounding metamorphic rocks recrystallized under the same granulite-facies metamorphic temperature conditions. The lower temperatures (520-670℃) obtained from garnet rim-biotite pairs probably correspond to the later, discrete amphibolite-facies event in the Mountains. departmental bulletin paper